Study of Virtual Molecular Docking of Avocados Compounds against Pseudomonas aeruginosa (5N5H) by Carbapenemase using DOCK 6 Algorithm - Hanidya Fidela Ulayya; Arifa Nursayyida; Fabiola Irianty Atmaja; Broto Santoso (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Antimicrobial resistance from bacteria is a global health problem that can cause death, and the cause is the emergence of carbapenem resistance Pseudomonas aeruginosa through VIM (Verona integron-encode metallo-β-lactamase), which causes the carbapenem class of antibiotics not to work properly. This species is a gram-negative bacteria which is the main cause of nosocomial pneumonia infection. This study aims to determine in silico inhibitory activity of 50 compounds obtained from avocado (Persea Americana Mill) on VIM, preventing carbapenem antibiotic resistance. The molecular docking process was carried out to test carbapenem's antibiotic resistance control activity by 50 compounds. Docking using DOCK 6 software with a flexible and rigid method, Molecular docking on a protein with PDB ID 5N5H, The target protein was prepared using the Chimera application. Visualization of ligand-protein interactions was carried out with PyMOL and PLIP. The results of the native ligand grid score obtained by each method are -63.013 kcal/mol (Flexible) and -64.032 kcal/mol (Rigid). The best test ligands in the flexible method are 44257090, 14282775 and 44257819, and the grid score are -77.474, -75.274 and -73.219 kcal/mol. The best test ligands in the rigid method are 5280637, 14282775 and 5490064; the grid score is -62.191, -61.714, and -60.453 kcal/mol. The results of the test ligands can provide a better grid score than native ligands, namely in the flexible method. However, the rigid method of grid score results is no better than the native ligand. A good result is that the test ligand grid score is smaller than native ligands, so it has less energy to bind to the active site.